In Silico Preliminary evaluation of Cx601 as new therapeutic approach in hospital clinical paths. (20th October 2021) - Rubba, F; Luglio, G; Castiglione, F; Rispo, A; Tropeano, FP; Pagano, G; Vozzella, EA; De Palma, GD
Abstract: : Crohn's disease is a chronic inflammatory bowel disease characterized by transmural inflammation and fistula formation. Perianal fistulas are a common complication of Crohn's disease and are estimated to affect up to 28% of patients in the first two decades after diagnosis, particularly those with colonic disease and rectal involvement. Complex perianal fistulas in Crohn's disease are challenging to treat, severely impair patients' quality of life and cause substantial morbidity. Allogeneic, expanded, adipose-derived stem cells (Cx601) are a promising new therapeutic approach, although their high cost is often discouraging. We aimed at assessing the safety and efficacy of this treatment in patients with complex perianal fistulas in patients with Crohn's disease. Therefore, we conducted a meta-analysis in order to evaluate this new therapeutic approach before introducing it as standard of care. We examined 8 studies published in the last 10 years, 5 of which were selected for the final analysis. The primary outcome assessed was the combined fistula remission (clinical + imaging) assessed through the clinical examination and MRI, the control being the traditional medical strategies (ie, antibiotics, immunomodulators and anti-tumour necrosis factor agents). We registered a total of 128 events (lack of remission) in the control group vs 94 in the experimental one (Confidence Interval for OR of 0, 12-0, 31, P < 0, 001). Our "in silico" assessment is reliable, being the introduction of (Cx601) an innovative and effective treatment. Further insights will be provided by the INSPIRE registry, a multinational post-marketing study whose main objective is the evaluation of the real-world clinical effectiveness and safety of (Cx601) in patients affected by Crohn's disease with complex perianal fistulas for a duration of 36 months, to which our University "Federico II" is actively taking part. Key messages: Disability reduction is an important goal in cronh therapeutic path of care. Our "in silico" assessment may support the introduction of (Cx601) an innovative and effective treatment.